Development of a mathematical model of the process of biological treatment of gasous effluents from formaldehyde - Бахарєва, Ганна Юріївна; Шестопалов, Олексій Валерійович; Філенко, Олеся Миколаївна; Тихомирова, Тетяна Сергіївна (Eastern-European Journal of Enterprise Technologies, 2016)
Experimental studies found the kinetic characteristics of oxidation of formaldehyde in gaseous effluents by microbial association. The quantitative values of the kinetic characteristics of formaldehyde destruction indicate the technological possibility of using a biological method of treatment of gaseous effluents from formaldehyde. It is found that the specific rate of oxidation of formaldehyde (CH2O) depends on its concentration and a maximum biomass - 45 and 275 mg/g for aerobic and anaerobic processes, respectively. This fact testifies to higher efficiency of formaldehyde detoxification under anaerobic denitrification than under aerobic oxidation. On the basis of experimental studies, a mathematical description of the processes occurring in the filled reactor vessel due to changes in the concentration of inflowing pollutants is developed. Using the found analytical relationships, an algorithm to calculate the changes in the average formaldehyde concentration in the vessel under continuous pollution is elaborated. The results allow making science-based design calculations of the process of biochemical treatment of formaldehyde.